Character Focalization in Children's Novels - Philpot, Don K. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book offers a comprehensive analysis of character focalization in ten contemporary realistic children's novels. The author argues that character focalization, defined as the location of fictional world perception in the mind of a character, is a prominent textual structure in these novels. He demonstrates how significant meanings are conveyed in a variety of forms related to characters' personal and interpersonal experiences. Through close analysis of each text, moreover, he exposes distinctive perceptual, psychological, and social-psychological patterns in the opening chapters of each novel, which are thereafter developed by the principles of continuation, augmentation, and reconfiguration. This book will appeal to scholars, teachers, and students in the fields of narrative studies, stylistics, children's literature scholarship, linguistics, and education.- Resumé vydavatel
Keywords: dětská literatura; vývojová psychologie; naratologie; pragmatika; children's literature; developmental psychology; narratology; pragmatics; elektronické knihy; studie; electronic books; studies